Boosting tenth graders' reading comprehension through the implementation of think pair share - Silfia, Silfia; Thamrin, Nur Sehang; Munawwarah, Munawwarah; Darmawan, Darmawan; Wahyudin, Wahyudin (Measurement In Educational Research, 2025)
This research aims to improve the reading comprehension of tenth-grade students of SMA Negeri 1 Parigi Tengah through the Think Pair Share (TPS). A quasi-experimental research design was employed, involving 60 tenth-grade students divided into experimental and control groups. The researcher used purposive sampling to select the sample, ensuring the chosen classes met the criteria for this research.  The experimental group was taught using the TPS method, while the control group received traditional instruction. Data were collected through pre-tests and post-tests and analyzed using statistical methods. The results of the data analysis showed a significant improvement in the reading comprehension scores of the experimental group compared to the control group. This was demonstrated through hypothesis testing. Applying a 0.05 level of significance and a degree of freedom (df) is 58, showed that t-counted 4.62 is higher than the t-table value 2.00. In conclusion, the use of the Think Pair Share method is effective in improving the reading comprehension students.